2020
DOI: 10.1371/journal.pone.0234543
|View full text |Cite|
|
Sign up to set email alerts
|

Gender differences in quality of life in coronary artery disease patients with comorbidities undergoing coronary revascularization

Abstract: In comparison to male patients with coronary artery disease, female patients suffer from more comorbidities, experience symptoms of coronary artery disease differently and report poorer health-related quality of life (HRQoL) after coronary revascularization. However, there is limited data on the impact of comorbidity burden on the recovery in HRQoL in female and male patients. We investigated the impact of comorbidity burden on the change in HRQoL following coronary revascularization in female patients versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
3
17
0
1
Order By: Relevance
“…Regarding the countries where the studies were performed, n = 3 were conducted in the USA ( n = 3) [ 14 , 15 , 16 ] and n = 5 in Sweden [ 17 , 18 , 19 , 20 , 21 ]. Of the selected studies, which were performed between 1997 and 2020, 11 involved elective surgery [ 22 , 23 , 24 , 25 ]. The 16 studies evaluated quality of life prior to surgery, coinciding with the preoperative angiography performed at the surgical hospitalisation appointment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding the countries where the studies were performed, n = 3 were conducted in the USA ( n = 3) [ 14 , 15 , 16 ] and n = 5 in Sweden [ 17 , 18 , 19 , 20 , 21 ]. Of the selected studies, which were performed between 1997 and 2020, 11 involved elective surgery [ 22 , 23 , 24 , 25 ]. The 16 studies evaluated quality of life prior to surgery, coinciding with the preoperative angiography performed at the surgical hospitalisation appointment.…”
Section: Resultsmentioning
confidence: 99%
“…Physical problems improved according to the functional capacity of the patients prior to surgery [ 14 ]. Female sex [ 18 , 29 ], age, hypertension, obesity, renal failure, cerebrovascular disease, unstable angina [ 28 ], being a smoker, and having a psychiatric pathology [ 16 ] are all factors that have been shown to delay the recovery of post-surgery quality of life [ 19 , 20 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literature also support these findings that QOL is better in males than females who underwent same PCI procedure. [16][17][18] Uchmanowicz et al also found that female patients scored lesser than males in all domains of SF-36. 19 It may be due to the fact that females are at greater risk recurrent angina post PCI as compared to males.…”
Section: Discussionmentioning
confidence: 92%
“…Gender and age are well known predictors of QoL [ 20 ]. Female patients with CAD have more age than male counterparts and therefore experience comparatively poorer HRQOL [ 31 ]. Our study has found a significant association between utility value and gender (P = 0.042) but not with VAS value, however, the mean VAS value was more in males than females.…”
Section: Discussionmentioning
confidence: 99%